Analysis of Blimp-1 and PD-1/PD-L1 Immune Checkpoint in an Autoimmune Thyroiditis Animal Model. (17th February 2020) - Zhang, Xue; Lv, Xiaoshu; Chen, Mengya; Liu, Haixia
Abstract : Objective . B lymphocyte-induced maturation protein 1 (Blimp-1) and programmed cell death protein 1 (PD-1) have opposing roles in the development of T cells; however, the mechanism of autoimmune thyroiditis- (AIT-) associated abortion is unclear. The present study investigated the expression of Blimp-1 and PD-1/PD-ligand 1 (PD-L1) in AIT-associated pregnancy loss and elucidated the related signaling pathway involving in the inflammatory response. Methods . An experimental fetal loss model with autoimmune thyroiditis was established after murine thyroglobulin- (mTg-) immunized CBA/J female mice mating with Balb/c males. ELISA was employed to investigate the TgAb level in the serum of CBA/J female mice. The expression of Blimp-1, PD-1/PD-L1, mammalian target protein rapamycin (mTOR), and Foxp3 proteins in the placenta and spleen was detected through immunofluorescence staining and western blotting. Results . ELISA indicated that the serum TgAb level in the mTg group was higher than that in the control group (P < 0.001 ). Fetal resorption rates increased in the mTg group compared with those in the control group (45.63% vs. 3.1%, P < 0.05 ). Blimp-1 levels in the placenta and spleen were higher in the AIT-related miscarriage group than in the control group. However, the expression of PD-1/PD-L1 and Foxp3 was significantly decreased in the placenta and spleen in the AIT-related miscarriage group. Conclusion . Blimp-1 participates in the pathogenesis of autoimmune thyroid disease-associated pregnancy loss through the inflammatory immune response, which is potentially mediated through the PD-1/PD-L1 signaling pathway.